Cyprus : Staff Report for the 2000 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2000)
Cyprus's economic performance in the past quarter century has been impressive but volatile, as the economy has come to rely on tourism as the main engine of growth. Financial market restrictions, including the interest rate ceiling, limit the ability of the Central Bank of Cyprus to manage liquidity. Capital and financial market liberalization are planned to be implemented by the time of EU accession. Executive Directors commended the authorities for their efforts to improve the oversight of the offshore financial sector.